Analisis Pelaksanaan Fungsi Pada Bagian Human Capital & General Affairs - Suci Fadila Safitri; Futri Shaheera; Kamaruzaman; Adam Victor Handoyo (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
This article analyzes the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Internship Program at PT TASPEN (Persero) Tanjungpinang Branch Office from February 9 to May 29, 2026. The discussion focuses on activities carried out in the Human Capital & General Affairs (HC & GA) department, which include managing the digital data input system for the Partnership and Community Development Program (PKBL) through the SAP application, digital records management, including inputting office expenses, asset reconciliation, inputting stationery stock, archiving expense notes, and filling out deposit checks and deposit slips, in addition to managing physical records and other operational support activities. The method used is a descriptive-analytical method based on direct work experience (experiential learning), supplemented by participatory observation and document study. The analysis shows that the internship activity successfully connects theoretical management concepts particularly in the areas of financial administration, HR management, and information systems with real-world work practices. The main obstacles identified were the adaptation process to the SAP system and the demand for high accuracy in data processing. These obstacles were overcome through active consultation, mentorship, and the application of the double-check principle. The MBKM internship program has proven effective in improving students' technical and non-technical competencies, while strengthening professional values aligned with the AKHLAK culture implemented within the state-owned enterprise (BUMN) environment.